Linguistic coherence in biblical Hebrew texts arrangement of information, participant reference devices, verb forms, and their contribution to textual segmentation and coherence - Regt, Lénart J. de 1960- (Piscataway, NJ Gorgias Press, 2019)
Shifts in participant reference -- Speaker, addressee, and communication flow in the discourse : presupposed and unexpected information; the verbal system; domains; con-chronological arrangement; segmentation -- Information in the text, focus, and word order in the clause -- Lexical cohesion and impact of individual words and phrases on the text as a whole -- Linguistic coherence in the Balaam pericope -- Conclusion and suggestions for further research.
"This monograph explores the distinct ways in which four discourse devices participate in establishing coherence in Biblical Hebrew texts. Bringing together linguistics, literary analysis, pragmatics, and translation methodology, de Regt demonstrates how a thorough understanding of the functions of devices of linguistic coherence beyond the sentence level should be integrated into biblical translation methodology and Biblical Hebrew pedagogy"--
"The present work is a revised and extended edition of the mémoire de synthèse of 2016"-- Author's preface
Includes bibliographical references and index
Keywords: Bible -- Criticism, Textual; Bible -- Language, style; Hebrew language -- Grammar; Cohesion (Linguistics); Hochschulschrift